2002
DOI: 10.1046/j.1468-1293.2002.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐line ritonavir/indinavir 100/800 mg twice daily plus nucleoside reverse transcriptase inhibitors in a German multicentre study: 48‐week results

Abstract: Ritonavir/indinavir 100/800 mg twice daily appears to be effective up to 48 weeks despite high baseline viraemia and low CD4 cell count in antiretroviral-naive patients. However, discontinuation due to adverse events, especially nephrotoxicity, is frequent and limits treatment duration. Therefore, extra hydration appears inevitable with this combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…The incidence of renal colic was prospectively estimated at 23.6% over 2 years in a cohort of 555 patients treated with a HAART regimen, including indinavir [42]. In a prospective study over 48 weeks evaluating the association of ritonavir/indinavir, 100/800mg twice daily in a HAART regimen, 19 (33%) out of 57 patients discontinued study medication because of nephrolithiasis [43].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…The incidence of renal colic was prospectively estimated at 23.6% over 2 years in a cohort of 555 patients treated with a HAART regimen, including indinavir [42]. In a prospective study over 48 weeks evaluating the association of ritonavir/indinavir, 100/800mg twice daily in a HAART regimen, 19 (33%) out of 57 patients discontinued study medication because of nephrolithiasis [43].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…In a series of 240 patients started on indinavir therapy, approximately 8% developed symptomatic nephrolithiasis and 20% developed crystalluria without symptoms [25]. Voigt et al [26] found a higher, 33% incidence of nephrolithiasis, in their series of 57 patients who received indinavir therapy over a 48-week observation period. Likewise, Gagnon et al [24] found a 67% prevalence of crystalluria among their study participants treated with this protease inhibitor.…”
Section: Acute Tubular Necrosismentioning
confidence: 98%
“…Likewise, Gagnon et al [24] found a 67% prevalence of crystalluria among their study participants treated with this protease inhibitor. Alkaline urine and volume depletion can lead to the formation of insoluble indinavir crystals [24][25][26]. The incidence of AKI in the setting of indinavir varies but may be as high as 25% [25,[27][28][29].…”
Section: Acute Tubular Necrosismentioning
confidence: 99%
“…Boosting of indinavir was not broadly implemented because of high plasma peak levels of the PI leading to enhanced renal toxicity (Voigt et al 2002;Boyd et al 2006). Boosting did not greatly enhance the bioavailability of nelfinavir.…”
Section: Second-generation Protease Inhibitor Therapy; Boosting Of Prmentioning
confidence: 99%